2021
DOI: 10.3389/fmed.2021.595077
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Clustering Reveals Sarcoidosis Phenotypes Marked by a Reduction in Lymphocytes Relate to Increased Inflammatory Activity on 18FDG-PET/CT

Abstract: Introduction: Sarcoidosis is a T-helper cell mediated disease characterized by granulomatous inflammation. We posited that unsupervised clustering of various features in sarcoidosis would establish phenotypes associated with inflammatory activity measured by 18FDG-PET/CT. Our goal was to identify unique features capable of distinguishing clusters and subsequently examine the relationship with FDG avidity to substantiate their potential use as markers for sarcoidosis inflammation.Methods: We performed a retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 48 publications
0
13
1
Order By: Relevance
“…Despite these defects, vaccine induced development and persistence of neutralization antibodies in sarcoidosis subjects is a particularly important and reassuring finding. However, it is worth noting the median peripheral absolute lymphocyte count (1.8 x 10 9 cells/liter) in our cohort is greater than previously described thresholds of significant sarcoidosis-related lymphopenia [34]. This suggests lymphopenia is unlikely to be a significant disease manifestation in this cohort and therefore may explain the preserved nAb activity.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Despite these defects, vaccine induced development and persistence of neutralization antibodies in sarcoidosis subjects is a particularly important and reassuring finding. However, it is worth noting the median peripheral absolute lymphocyte count (1.8 x 10 9 cells/liter) in our cohort is greater than previously described thresholds of significant sarcoidosis-related lymphopenia [34]. This suggests lymphopenia is unlikely to be a significant disease manifestation in this cohort and therefore may explain the preserved nAb activity.…”
Section: Discussioncontrasting
confidence: 58%
“…Sarcoidosis is a T cell mediated disease characterized by local CD4+ T lymphocyte inflammation and peripheral lymphocyte depletion in severe or active disease, as well as anergy and exhaustion in progressive disease [4,5,33,34]. Defects within humoral immunity have also been described and include evidence of B cell hyperactivation, autoantibody production, decreased circulating memory B cells, as well as previously mentioned impaired serologic responses to Tetanus and Hepatitis vaccines [10,11,20,[35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study, which enrolled 30 patients with untreated sarcoidosis measured various biomarkers including soluble interleukin-2 receptor (sIL-2R), C-reactive protein (CRP), ACE, and urine calcium in addition to splenic FDG uptake on PET and found that there was a significant linear correlation between sIL-2R and SUVmax on PET [ 32 ]. It has also been shown that a reduction in absolute peripheral CD4+ T-lymphocyte count is associated with increased PET activity and possibly serves as a proxy for inflammatory activity [ 33 ▪ ]. A less commonly known laboratory marker, serum chitotriosidase, was found to be significantly correlated with PET activity whereas no correlation was found with ACE [ 34 ].…”
Section: Correlation Of Pet With Biomarkersmentioning
confidence: 99%
“…The interactions between lymphocytes, macrophages, and immune mediators, such as tumor necrosis factor alpha (TNF-a) and interferon gamma (IFN-g), lead to an exaggerated and polarized CD4+ T-helper (Th) 1 and Th17 cell response against an unknown antigenic stimulus at sites of granuloma formation (2). While local CD4+ T-cell accumulation, proliferation, and activation are invariably observed within affected tissues, 10-50% of those with sarcoidosis paradoxically exhibit peripheral lymphopenia coupled with anergy or exhaustion (3)(4)(5)(6)(7)(8). When present, lymphopenia specifically related to low CD4+ T-cell counts, has been linked with greater inflammatory activity in sarcoidosis (7).…”
Section: Introductionmentioning
confidence: 99%
“…While local CD4+ T-cell accumulation, proliferation, and activation are invariably observed within affected tissues, 10-50% of those with sarcoidosis paradoxically exhibit peripheral lymphopenia coupled with anergy or exhaustion (3)(4)(5)(6)(7)(8). When present, lymphopenia specifically related to low CD4+ T-cell counts, has been linked with greater inflammatory activity in sarcoidosis (7).…”
Section: Introductionmentioning
confidence: 99%